The Identification of the Way Ratai Geothermal System and Menanga Fault Through Derivative Analysis and 3D Modeling of Gravity Data: Case Study in Tanggamus Regency, Lampung - Ilham Dani; Virna Amelia; Rifanny Dwi Anwar; Nayla Julita Putri (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2026)
The gravity method is one of the most commonly used geophysical exploration methods for deep ground structure, especially in the geothermal prospect area. In this study the Way RataiGeothermal System and Menanga Faulthave been successfully identified in PesawaranRegency, Lampung Province using full Bouguer anomaly informations. The interpretation process was also performed through the First Horizontal Derivative (FHD), besides the Second Vertical Derivative (SVD) to emphasize anomalies whilst mapping density contrast limits related with fault and fracture-zones. The subsequent step was to predict the rock density distribution and to assist in interpreting the subsurface geology, 3D modelling was conducted. Results of interpretations show a low density area related to the Way Ratai geothermal system and linear anomaly patterns, which are believed to correspond the Menanga Fault. These results indicate that there are permeable bodies which act as pathways for the hydrothermal fluids to migrate. The tectonic control has been proved to be the significant preparation mechanism for geothermal system. In general, it has proved that the derivative or 3D modeling of the gravity method would be viable in geothermal survey.